History of co-occurring disorders and current mental health status among homeless veterans - Kele Ding; Matthew Slate; Jingzhen Yang (BMC, 2018)
Abstract Background Homeless veterans are at high risk for co-occurring disorders (COD), defined as mental illnesses that include at least one alcohol or other drug use disorder and at least one non-drug related mental disorder. However, epidemiological studies examining the prevalence of COD and associated mental health status in this population are limited. The objectives of the study were: (1) to describe a history of diagnosed mental disorders among homeless veterans admitted to a transitional housing program, and (2) to examine the associations of the prior diagnosed COD and other mental disorders with current mental health status. Methods Study participants were male homeless veterans admitted to a transitional housing program from July 2015 to September 2017 in a large municipal area in Northeast Ohio, the United States. Cross-sectional, self-reported data from the admission assessment were included and analyzed. History of mental disorder diagnoses were aggregated into five categories for the purpose of this study: no mental disorders, only alcohol or other drug use disorder(s), one non-drug related mental disorder, two or more non-drug related mental disorders, and COD. Current mental status were measured as empowerment, mental component summary score (MCS) and physical component summary score (PCS) of health related quality of life (VR-12), and perceived overall well-being. Sample distribution of the five categories and their associations with current mental status were examined using Generalized Linear Model test. Results Of all participants, 76.7% had at least one prior diagnosed mental disorder, including 47.4% with any drug-related disorders. Over one-third (37.2%) reported having COD. Compared to those with no mental disorder history, those with COD scored significantly lower on MCS and empowerment scores; those with any prior diagnosed non-drug related mental disorders also scored significantly lower on MCS. No significant differences, however, were found in current mental health status between those with COD and those with mental disorders but not COD. Conclusions COD prevalence among homeless veterans was within the parameter of other literature reports. Veterans with COD compared to veterans with no history of mental disorders tended to have lower MCS and empowerment scores. Veterans with COD had the same mental health status as those with other mental disorders.